Corrosion Resistance of Finer/Coarser Pearlitic Structures of Carbon Steel. Issue 4 (6th April 2021) - Murase, Yoshiharu; Masuda, Hiroyuki; Katayama, Hideki
Abstract : Corrosion performance on pearlite structures of carbon steels has been researched using scanning Kevin probe force microscopy and energy-dispersive X-ray spectroscopy. The corrosion test was conducted by immersing in borate buffer solution containing NaCl. In the coarser pearlite structure, we detected an increase in the Volta potential at pearlitic cementite–ferrite boundaries after corrosion, in accordance with the following: increasing C concentration, and decreasing Mn concentration. We detected little change in the Volta potential and inorganic element concentrations in the finer pearlite structures. Crack-like trenches, with a depth less than several nanometers, formed along the boundaries where the Volta potential increased in the coarser pearlite structures. We demonstrated the importance of the concentration of inorganic elements (such as Mn and C) in promoting the initiation of corrosion, and higher corrosion susceptibility for the coarser pearlite structures.